'True Anzacs', Yanks and 'yikes': New Zealanders on the Australian home front during the Second World War. Issue 3 (3rd July 2021) - Leach, Daniel
Abstract: This article explores the New Zealand presence on the Australian home front during WW2, from experiences of troops in transit to the local activities of NZ voluntary aid detachments. While much has been published regarding American and other forces in wartime Australia, those from our closest regional ally have not received the same attention. Employing contemporary accounts and archival sources, this article establishes New Zealanders in their rightful place in the Australian wartime story — albeit not without controversy. The NZ 'occupation' of Norfolk Island is also explored; one of the lesser-known stories of WW2 on both sides of the Tasman.